Snyder-Robinson syndrome presenting with learning disability, epilepsy, and osteoporosis: A novel SMS gene variant - Megumi Leung; Meredith Sanchez-Castillo; Newell Belnap; Marcus Naymik; Anna Bonfitto; Jennifer Sloan; Katie Hassett; Wayne M. Jepsen; Aravind Sankaramoorthy; Tracy Murray Stewart; Jackson R. Foley; Sampathkumar Rangasamy; et al. (Rare)
Snyder-Robinson syndrome (SRS) is a rare X-linked recessive disorder characterized by a collection of clinical features including mild to severe intellectual disability, hypertonia, marfanoid habitus, facial asymmetry, osteoporosis, developmental delay and seizures. Whole genome sequencing (WGS) identified a mutation in the spermine synthase (SMS) gene (c.746 A>G, p.Tyr249Cys) in a male with kyphosis, seizures, and osteoporosis. His phenotype is unique in that he does not have intellectual disability (ID) but does have a mild learning disability. This case demonstrates a milder presentation of SRS and expands the phenotype beyond the reported literature.